New patterns in China's water footprint: Analysis of spatial and structural transitions from a regional perspective. (1st February 2020) - Xiong, Yiling; Tian, Xin; Liu, Shangwei; Tang, Zhipeng
Abstract: China faces a major challenge to support the operation and development of an enormous economy with limited water resources. Decoding the way that the final demand influences water consumption patterns is helpful for understanding the discrepancy between water supply and demand. Especially in the current time, when China has experienced socioeconomic transition and its government has proposed a series of water conservation policies over the years, exploring the transition in the water consumption pattern is necessary for further water conservation in China. Meanwhile, there exist distinct economic levels and stages of development among provinces, making it necessary to develop more refined water management strategies in the various provinces. This study comprehensively investigates the trend, spatial distribution and structure of the water footprint in mainland China. Furthermore, it explores the effects of socioeconomic factors on transitions in water footprint patterns with the aid of multi-regional input–output analysis, structural decomposition analysis, and linear regression. The results show that the water footprints of almost all the provinces were decoupled from economic growth from 2007 to 2012. Several northern provinces dramatically increased their water footprints, further enlarging the difference between north and south. The north also showed a wider urban–rural gap in per capita water footprint than did the south. From the viewpoint of structural transitions, household consumption (as the primary contributor) remained stable while an obvious increase in the water footprint was induced by fixed capital formation, in which agriculture and strategic emerging manufacturing played important roles. From the perspective of driving forces, water intensity improvement and changes in the final demand structure saved water. However, these effects were counteracted by the change in the final demand level and the composition of the final products. By identifying China's water footprint patterns and its transitions, our results clarify China's strategic water demand pattern and provide refined insights for future water conservation. Highlights: Transitions in distribution and structure of China's water footprint is identified. Water footprint decoupled by efficiency improvement and structural optimization. North-south gap enlarged with growingly higher per capita water footprint in north. Household consumption, as primary source of water footprint, remained stable. Growth of water footprint was mainly induced by fixed capital formation.